Provider Perspectives on Barriers and Facilitators to Postpartum Care for Low-Income Individuals - Rachel S. Ruderman; Emma C. Dahl; Brittney R. Williams; Ka'Derricka Davis; Joe M. Feinglass; William A. Grobman; Michelle A. Kominiarek; Lynn M. Yee (Women's Health Reports, 2021)
Background: Recent paradigm shifts in postpartum care have conceptualized the ?fourth trimester? as a critical transitional period requiring tailored, ongoing health care. However, this concept presents challenges for providers, especially in low-resource settings. Our objective was to understand providers' perspectives on challenges in postpartum care to highlight strategies for optimizing care. Methods: Focus groups were conducted using a semistructured interview guide to elicit perspectives on barriers and facilitators to postpartum care. Participants included physicians, nurses, and social workers who care for low-income postpartum individuals. Interviews explored the provider experience of postpartum care, with a focus on barriers experienced by patients and providers, and tools for maintaining engagement. Analysis was performed using the constant comparative method and framed by the Social Ecological Model. Results: Participants (N?=?26) all acknowledged the importance of the ?fourth trimester? but identified multiple barriers to providing optimal postpartum care. Challenges providers perceived for patients and those they perceived for themselves often overlapped, including difficulty with appointment scheduling, insurance limitations, lack of provider continuity, and knowledge gaps. Providers identified ease of referrals to specialists, access to tangible services (e.g., contraception), and enhanced care coordination (e.g., patient navigation) as potential facilitators of improved postpartum care. Conclusions: Obstetric providers recognize the importance of postpartum care yet highlighted significant systems- and patient-based barriers to achieving optimal care. The development and implementation of postpartum care delivery system redesign, such as the use of patient navigators to improve health care utilization and resource attainment, may enhance care during this critical time. Clinical Trial No.: NCT03922334.